2010
DOI: 10.1111/j.1468-3148.2010.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and Fathers at Play with their Children with Down Syndrome: Influence on Child Exploratory and Symbolic Activity

Abstract: Background-Through play children exercise their emerging mental abilities, and for their part, when in collaborative play, caregivers often adjust their behaviours to assist their children's progress. In this study, we focused on comparisons between play of Down Syndrome (DS) children with their two parents as well as on comparisons between the two parents' play behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Observations took place at the Intervention Center in a small, quiet room, which was familiar to the participants. The findings of previous studies using 10-min observations of play lend credence to the validity of these temporal parameters (see Bornstein et al, 1996; Bornstein and Tamis-LeMonda, 1997; de Falco et al, 2008, 2010; Bentenuto, 2012). …”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…Observations took place at the Intervention Center in a small, quiet room, which was familiar to the participants. The findings of previous studies using 10-min observations of play lend credence to the validity of these temporal parameters (see Bornstein et al, 1996; Bornstein and Tamis-LeMonda, 1997; de Falco et al, 2008, 2010; Bentenuto, 2012). …”
Section: Methodssupporting
confidence: 53%
“…Second in our study we used an observation at single point, so longitudinal studies are needed to follow the development of these children’s play across time. Future work should also consider associations between parents’ positive affect and sensitivity and the level of specific abilities child’s play (Bornstein et al, 2002; Venuti et al, 2008; de Falco et al, 2010). However, this study has some important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This influences behaviors by providing adequate scaffolding during cooperation which involve more sophisticated behaviors and underlying mental skills resulting in more exploratory and symbolic activity. A positive correlation has been found between the quality of affective parent–child interaction and the exploratory and symbolic skills of children with Down syndrome 2931. Nevertheless, it is important to emphasize that this is a pilot study based on a small case series and we recognize its shortcomings.…”
Section: Resultsmentioning
confidence: 89%
“…Twenty-three studies indicated that the data came from parents or caregivers [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Authors of 16 studies reported that the mother was the sole respondent for all data [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%